Learners' interest in online learning of mathematics - Esti Harini; Yohanes Sugeng Riyono; Annis Deshinta Ayuningtyas; Sai Hoe Fu (UNION : Jurnal Ilmiah Pendidikan Matematika, 2023)
This study aims to determine (1) The extent of the tendency of students' interest in learning mathematics online. (2) To what extent the tendency of students' interest in learning mathematics towards the use of Zoom Meeting and Google Classroom. This research is a descriptive research with a qualitative approach. The research was conducted at SMP Kanisius Sumber Dukun with a sample of 30 students selected using Purposive Sampling technique. Data collection techniques using observation, interviews, questionnaires, and documentation. The research instruments used were interview guidelines and interest questionnaires. While data analysis techniques using data triangulation include data reduction, data presentation and conclusion drawing. The results of this study indicate that (1) The tendency of students' interest in learning mathematics online is included in the high category with a percentage of 72.01%. (2) The tendency of students' interest in learning mathematics whose learning uses Zoom Meeting is included in the very high category with a percentage of 77.42%, while the learning interest of students whose learning uses Google Classroom is included in the very low category with a percentage of 22.58%. This means that the tendency of mathematics learning interest of Kanisius Sumber Junior High School students towards the use of Zoom Meeting is higher than Google Classroom.